2021
DOI: 10.9734/jabb/2021/v24i630219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consuming Different Varieties of Bambara Nut (Vigna subterranea) Seeds on Liver and Kidney of Diabetic and Non-diabetic Subject

Abstract: Aims: Bambara nut seeds have been reported as a good source of food with high fiber and nutritional contents, and is consumed by persons with diabetes as one of the dietary therapy. However, the plant seeds are of different varieties and whether they might have vary biological effects on renal and liver functions is not fully known. This has prompted the study to evaluate effects of consuming different varieties of Bambara Nut seeds on liver and kidney of both diabetic and non-diabetic rats. Methodology:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Bambara groundnut seed is reported to possess high fiber and good nutritional content where its consumption was reported to ameliorate diabetes and its related complications 16,17 . It is locally used as one of the daily dietary therapy for persons with diabetes in northern part of Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bambara groundnut seed is reported to possess high fiber and good nutritional content where its consumption was reported to ameliorate diabetes and its related complications 16,17 . It is locally used as one of the daily dietary therapy for persons with diabetes in northern part of Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Study showed that consumption of fermented diet of Bambara groundnut seeds improved antioxidant regimen in experimentally induced diabetes 1,16 . In a recent study by the authors, consumption of feed formulated from the plant seeds was reported to be safe and has the potential to ameliorate diabetic hepatic and renal failure in rats 17 . A lot of traditional foods which found to have fewer/no side effects, low cost, ready available and possess both dietary and therapeutic functions have been encouraged to be developed as nutraceutics 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation